Resilience and Interpersonal Skills Shape Work Readiness of ORMAWA Students: Resiliensi dan Keterampilan Interpersonal Membentuk Kesiapan Kerja Mahasiswa ORMAWA - Meha, Nurmala Lutfi; Imsar; Nasution, Muhammad Syukri Albani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In today’s competitive labor market, graduates must possess not only academic excellence but also strong soft skills to secure employment. Specific Background: Interpersonal skills, problem solving, and resilience have been identified as key competencies influencing employability. Knowledge Gap: However, limited studies have examined how student organizations (ORMAWA) contribute to these competencies in the context of Islamic higher education institutions. Aims: This study investigates the influence of interpersonal skills, problem solving, and resilience on the work readiness of ORMAWA FEBI UINSU students. Results: Using a quantitative method with 98 respondents and SEM-PLS analysis, results reveal that interpersonal skills and resilience significantly affect work readiness, while problem solving does not. Novelty: The study uniquely highlights resilience as the most dominant predictor and applies SEM-PLS to an entire population of active student organization members within an Islamic university context. Implications: These findings suggest the importance of integrating soft skills development, particularly resilience, into organizational and academic programs to better prepare students for the workforce.Highlight : Resilience is the most dominant factor influencing work readiness among student organization members at FEBI UINSU. Problem-solving skills showed no significant impact, indicating its development may need more structured practice. Active participation in student organizations (ORMAWA) strengthens interpersonal skills and mental adaptability. Keywords : Interpersonal, Problem Solving, Resilience, Job Readiness, ORMAWA Students